2020
DOI: 10.3390/md18120656
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Biofilm Formation by Modified Oxylipins from the Shipworm Symbiont Teredinibacter turnerae

Abstract: The bioactivity-guided purification of the culture broth of the shipworm endosymbiont Teredinibacter turnerae strain 991H.S.0a.06 yielded a new fatty acid, turneroic acid (1), and two previously described oxylipins (2–3). Turneroic acid (1) is an 18-carbon fatty acid decorated by a hydroxy group and an epoxide ring. Compounds 1–3 inhibited bacterial biofilm formation in Staphylococcus epidermidis, while only 3 showed antimicrobial activity against planktonic S. epidermidis. Comparison of the bioactivity of 1–3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…79 A culture of Teredinibacter turnerae yielded turneroic acid 250, an 18-carbon fatty acid decorated with hydroxy and epoxide moieties, that inhibited biolm formation. 80 The genus Verrucosispora was the source of new aminofurans, proximicins F 251 and G 252 and diproximicin A 253 that were obtained via overexpression of PPtase genes, 81 a siderophore named FW0622 254, 82 an abyssomicin polyketide 255, 83 and verrucosamide 256, a cytotoxic 1,4-thiazepane-containing thiodepsipeptide. 84 Genomic-metabolomic proling of Vibrio spartinae identied this proteobacteria as a producer of isoheptylprodigiosin 257, a new branched sidechain prodigiosin, 85 while chemical investigations of a Vibrio sp.…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…79 A culture of Teredinibacter turnerae yielded turneroic acid 250, an 18-carbon fatty acid decorated with hydroxy and epoxide moieties, that inhibited biolm formation. 80 The genus Verrucosispora was the source of new aminofurans, proximicins F 251 and G 252 and diproximicin A 253 that were obtained via overexpression of PPtase genes, 81 a siderophore named FW0622 254, 82 an abyssomicin polyketide 255, 83 and verrucosamide 256, a cytotoxic 1,4-thiazepane-containing thiodepsipeptide. 84 Genomic-metabolomic proling of Vibrio spartinae identied this proteobacteria as a producer of isoheptylprodigiosin 257, a new branched sidechain prodigiosin, 85 while chemical investigations of a Vibrio sp.…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…A culture of Teredinibacter turnerae yielded turneroic acid 250 , an 18-carbon fatty acid decorated with hydroxy and epoxide moieties, that inhibited biofilm formation. 80…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…Several marine-derived compounds were characterized to produce anti-biofilm properties with varying target domains, such as quorum sensing (QS)-inhibitor psammaplin A ( Oluwabusola et al, 2022 ), EPS-disruptor cyclic dipeptide ( L -Leucyl- L -propyl) ( Gowrishankar et al, 2014 ), pre-formed biofilm suppressor butenolide ( Yin et al, 2019 ), and bacterial aggregation downregulator rodriguesine A ( Lima et al, 2014 ). Three modified fatty acids were previously purified from the shipworm endosymbiont Teredinibacter turnerae 991H.S.0a.06 ( Lacerna et al, 2020 ). Turneroic acid, a new modified oxylipin characterized by an epoxide moiety and a hydroxy group, inhibited biofilm formation in S. epidermidis RP26A ( Lacerna et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three modified fatty acids were previously purified from the shipworm endosymbiont Teredinibacter turnerae 991H.S.0a.06 ( Lacerna et al, 2020 ). Turneroic acid, a new modified oxylipin characterized by an epoxide moiety and a hydroxy group, inhibited biofilm formation in S. epidermidis RP26A ( Lacerna et al, 2020 ). Preliminary structure-activity relationship (SAR) showed that trans -12,13-epoxyoctadecanoic acid ( 1 ) has a high selectivity index for anti-biofilm activity against S. epidermidis with no antiproliferative effects against MDCK NBL-2 cell line ( Lacerna et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation